DOLLARS & SCENTS: BUILDING BRAND-RELATIONSHIPS IN STORES - Marques, C.; Vinhas da Silva, Rui; Cardoso, B. (2020 Global Marketing Conference, 2020)
Scent marketing is used to modify consumer behavior by subconsciously creating emotions in people, thus shaping their decisions, which ultimately leads to higher consumer purchases (Madzharov et al., 2015; Krishna et al., 2014; Spence et al., 2014; Hultén, 2011). Companies use scent marketing to create positive memories and with this somehow influence consumers´ subsequent feelings about the brand, resulting in a lasting emotional bond with the consumer (ibid). Studies have focused on how senses really impact on consumer behaviour and emotions, but much of it has been done in a laboratory context, rather than in real stores. The current study differs from traditional approached in that it aims to understand the impact of scent in bricks and mortar retailing, namely on brand loyalty and brand image, i.e. specifically, the current study aims to shed light on how the introduction of a pleasant scent influences the emotional state of the consumer and his or her intention to buy product and revisit the store. Customer satisfaction with staff and the overall quality of the store are also evaluated as well as the moderation effect of store type. The experimental study started on June 5th and ended on July 8th of 2019. The first two weeks of the experience took place at the Worten Mobilat Amadora in Portugal and the last two weeks in the Worten Megastore at Amadora. In achieving more stable results, the stimulus was programmed to be switched on, on a particular day and switched off on the following day. A survey was conducted to evaluate if the introduction of a pleasant scent impacted, in a positive way on the intention to revisit the store, the overall store image, the perceived environmental quality of the store and the overall product and staff evaluation. Hypotheses testing via multiple regression analyses was adopted. Results show that the impact of the customer emotional state on intention to purchase and to revisit the store was not verified. In contrast, the introduction of a pleasant scent correlates positively with intention to revisit the store, overall store image, perceived environmental quality, overall evaluation of products and staff and negatively with perception of time spent in the store. Finally, there is no store type effect on attitudinal and behavioural outcomes. Theoretical and practical implications are discussed.